EFEKTIFITAS ALAT PERMAINAN BOARD GAME PADA PERKEMBANGAN ANAK TK - Ummi Masrufah Maulidiyah; Dzulkifli Dzulkifli; andini dwi arumsari (MOTORIC, 2022)
Abstract APE (Educational Game Tool) is a game tool designed to be a learning resource for children to get a learning experience. This experience will help improve all aspects of a child's development, including physical/motor, emotional, social, language, cognitive and moral. This board game trial was in accordance with the learning objectives and developmental level of early childhood because it was needed to improve children's understanding of animals and their habitats. Educational game tools optimize children's development according to their age and level of development. as long as they meet the requirements of children's growth and development in all aspects, are interesting, can be played in various ways, are not easily damaged, can be used by all accepting cultures. This study uses a type of research with a qualitative approach and conducts trials on early childhood students. This research was conducted at TK Aisyiyah Bustanul Athfal 52 which is located on Jalan Keputih, Keputih sub-district, Surabaya. The subjects in this study were 10 PAUD TK Aisyiyah students. The result of the research is that after the researcher conducted the trial 2 times, the students already understood and were able to play it. But there are still 1-2 children who still play it wrong. Keywords: Educational game tools, Giftedness, Child development, Children's understanding